The impact of parental unaffected allele combination on the diagnostic outcome in the preimplantation genetic testing for myotonic dystrophy type 1 in Japanese ancestry - Senba, Hiroshi; Sueoka, Kou; Sato, Suguru; Higuchi, Nobuhiko; Mizuguchi, Yuki; Sato, Kenji; Tanaka, Mamoru (Reproductive medicine and biology, 2020)
Purpose The objective is to clarify the practical problem of the preimplantation genetic testing (PGT) for myotonic dystrophy type 1 (DM1) in Japanese subjects. Methods For the 32 couples who consented to participate in PGT for DM1, CTG repeats number on the unaffected alleles was analyzed. Based on the allele combination, they were classified into 3 groups by the number of diagnostic allelic pattern; “full informative,” “semi informative,” and “noninformative.” According to the Japan Society of Obstetrics and Gynecology (JSOG) principle, PGT was performed using the direct diagnosis to the 288 embryos from the 17 couples who received the ethical approval from both our institution and JSOG. Results In the 32 couples, the frequency of CTG repeats on the unaffected alleles showed bimodal distribution. The “full informative,” “semi informative,” and “noninformative” couples accounted for 46.9% (15/32 couples), 46.9% (15/32 couples) and 6.2% (2/32 couples), respectively. The transferable embryos accounted for 28.9% (33/114 embryos) in the “full informative” couples, although it was limited to 12.6% (22/174 embryos) in the “semi informative” couples. Conclusion The loss of unaffected embryos which cannot be diagnosed as transferable was a clinically major problem and implied an increase in oocyte retrieval, especially for “semi informative” couples.